Roles and post‐translational regulation of cardiac class IIa histone deacetylase isoforms. (25th November 2014) - Weeks, Kate L.; Avkiran, Metin
Abstract Cardiomyocyte hypertrophy is an integral component of pathological cardiac remodelling in response to mechanical and chemical stresses in settings such as chronic hypertension or myocardial infarction. For hypertrophy to ensue, the pertinent mechanical and chemical signals need to be transmitted from membrane sensors (such as receptors for neurohormonal mediators) to the cardiomyocyte nucleus, leading to altered transcription of the genes that regulate cell growth. In recent years, nuclear histone deacetylases (HDACs) have attracted considerable attention as signal‐responsive, distal regulators of the transcriptional reprogramming that in turn precipitates cardiomyocyte hypertrophy, with particular focus on the role of members of the class IIa family, such as HDAC4 and HDAC5. These histone deacetylase isoforms appear to repress cardiomyocyte hypertrophy through mechanisms that involve protein interactions in the cardiomyocyte nucleus, particularly with pro‐hypertrophic transcription factors, rather than via histone deacetylation. In contrast, evidence indicates that class I HDACs promote cardiomyocyte hypertrophy through mechanisms that are dependent on their enzymatic activity and thus sensitive to pharmacological HDAC inhibitors. Although considerable progress has been made in understanding the roles of post‐translational modifications (PTMs) such as phosphorylation, oxidation and proteolytic cleavage in regulating class IIa HDAC localisation and function, more work is required to explore the contributions of other PTMs, such as ubiquitination and sumoylation, as well as potential cross‐regulatory interactions between distinct PTMs and between class IIa and class I HDAC isoforms.